Pengaruh Lingkungan Sosial terhadap Motivasi Belajar Siswa Kelas V SD Negeri 0101 Sibuhuan - Irma Sari Daulay; Ainun Naimi Pohan; Wira Astianingisih; Maya Sari Batubara; Nur Desi Nasution; Rahmadani Pulungan (Kampus Akademik Publiser, 2026)
This study aims to determine the influence of social environment on students' learning motivation at the elementary school level. The social environment in this context includes students' interactions with family, peers, and the school environment. This research employed a quantitative approach using a survey method. The subjects were fifth-grade students from a public elementary school, with a total of 17 respondents. The instrument used was a closed-ended questionnaire that had been tested for validity and reliability. Data analysis results showed a significant influence between the social environment and students' learning motivation, with a contribution percentage of 78%. Students who are in a supportive social environment tend to have higher learning motivation, as indicated by enthusiasm, curiosity, and active participation in learning activities. These findings suggest that the social environment plays a vital role in supporting students’ academic success. Therefore, collaboration among parents, teachers, and peers needs to be strengthened to create a positive learning atmosphere and foster students’ intrinsic motivation.